1
You visited us
1
times! Enjoying our articles?
Unlock Full Access!
Byju's Answer
Standard XII
Mathematics
First Fundamental Theorem of Calculus
Prove that a2...
Question
Prove that
a
2
2
a
b
b
2
b
2
a
2
2
a
b
2
a
b
b
2
a
2
=
a
3
+
b
3
2
Open in App
Solution
Let
LHS
=
∆
=
a
2
2
a
b
b
2
b
2
a
2
2
a
b
2
a
b
b
2
a
2
=
a
2
a
2
2
a
b
b
2
a
2
-
2
a
b
b
2
2
a
b
2
a
b
a
2
+
b
2
b
2
a
2
2
a
b
b
2
Expanding
=
a
2
a
4
-
2
a
b
3
-
2
a
b
b
2
a
2
-
4
a
2
b
2
+
b
2
b
4
-
2
a
3
b
=
a
6
-
2
a
3
b
3
-
2
a
3
b
3
+
8
a
3
b
3
+
b
6
-
2
a
3
b
3
=
a
6
+
2
a
3
b
3
+
b
6
=
a
3
2
+
2
a
3
b
3
+
b
3
2
=
a
3
+
b
3
2
=
RHS
Hence proved.
Suggest Corrections
0
Similar questions
Q.
Prove the following :
∣
∣ ∣ ∣
∣
2
a
b
a
2
b
2
a
2
b
2
2
a
b
b
2
2
a
b
a
2
∣
∣ ∣ ∣
∣
=
−
(
a
3
+
b
3
)
2
.
Q.
if
(
a
2
+
b
2
)
3
=
(
a
3
+
b
3
)
2
then
a
b
+
b
a
=
Q.
If (a
2
+ b
2
)
3
= (a
3
+ b
3
)
2
then find the value of (a/b) + (b/a)
Q.
If
(
a
2
+
b
2
)
3
=
(
a
3
+
b
3
)
2
and
a
b
≠
0
, then
(
a
b
+
b
a
)
6
is equal to
Q.
Choose the correct answer from the alternatives given.
If
(
a
2
+
b
2
)
3
=
(
a
3
+
b
3
)
2
, then
a
b
+
b
a
View More
Join BYJU'S Learning Program
Grade/Exam
1st Grade
2nd Grade
3rd Grade
4th Grade
5th Grade
6th grade
7th grade
8th Grade
9th Grade
10th Grade
11th Grade
12th Grade
Submit
Related Videos
Fundamental Theorem of Calculus
MATHEMATICS
Watch in App
Explore more
First Fundamental Theorem of Calculus
Standard XII Mathematics
Join BYJU'S Learning Program
Grade/Exam
1st Grade
2nd Grade
3rd Grade
4th Grade
5th Grade
6th grade
7th grade
8th Grade
9th Grade
10th Grade
11th Grade
12th Grade
Submit
AI Tutor
Textbooks
Question Papers
Install app